From National Presentation to International Cooperation : Exploring Cultural Cooperation in the Finnish and Estonian Theatre Festival fields - Kirves, Marja-Liisa (My University, 2019)
Estonia and Finland have a unique relationship sharing economic interests, Finno-Ugrian roots and cultural connections of tens of years. In this thesis I ask, how is this relationship portrayed in the cultural cooperation occurring between the nations today. My operational setting are arts organizations, and more specifically the theatre festival fields in both countries. I have conducted a mixed method desk research by gathering and analysing both qualitative and quantitative data from 15 Finnish and 13 Estonian theatre festivals. The theory section presents the concepts of Cultural Policy and Cultural Diplomacy to offer a more governmental viewpoint, and Cultural Cooperation and Strategic Management, to present the organizational aims of the theatre festival field. The first chapter presents the introduction and background to the subject. The second chapter presents the theory and the third discusses on the research methods and design. The fourth chapter presents the analysis and findings of the desk research as well as the analysis of the cultural policies of Finland and Estonia. The fifth chapter presents conclusions derived from the findings and the sixth discusses the conducted study and further research. The Estonian and Finnish theatre festival pools have similarities but are different in their international actions, funding schemes and in the booking of their programme. The Estonian festivals are highly international in their booking, and the cultural policy of Estonia as well as the offered funding schemes support international actions. The Finnish theatre festival field is more focused on domestic programming, which can also be reflected from their funding schemes. The Estonian festival pool books more, and more versatile Finnish programme compared to the Finnish festivals that do not focus on Estonian offering in general. The festival organizations between the two pools had not conducted cooperation, and other traces of a special connection between Finland and Estonia were also not found from the chosen sample. From the results, the performing arts groups have conducted the most cultural collaboration and would be an interesting target group for further research.
Keywords: kulttuuriyhteistyö; kulttuuripolitiikka; Suomi; Viro; festivaalit; teatteri; suomalais-ugrilaiset kansat; strategia; johtaminen; fi=taidehallinto|sv=Arts Management|en=Arts Management|